INCREASING THE EFFICIENCY OF THE DIGGER FOR PLANTING SEEDLINGSFRUIT TREES - RUTKEVYCH, VOLODYMYR; RIPA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The question of increasing the efficiency of the process of mechanization of planting fruit tree seedlings in conditions of changing technological load on working bodies is considered. The reasons that restrain the development of industrial production of horticulture are mentioned, among which the low level of mechanization and the absence of proper technical support should be highlighted. In Ukraine, there is practically no production of specialized garden equipment, and what is produced is significantly inferior to foreign analogues, which leads to violations of agrotechnical measures and high labor intensity of production.In order to reduce the energy consumption of the process of digging pits for fruit tree seedlings, a new structural and technological scheme of a hydraulic pit digger with an energy-saving hydraulic drive of working bodies is proposed. The developed energy-saving system of the hydraulic drive of the working bodies of the hydraulic pit digger allows to coordinate the operating modes of the executive hydraulic motors with variable technological load on the working bodies of the pit digger. The system involves adjusting the feed of the screw of the digger in accordance with the change in the digging force acting on the digging mechanism, as a result of which stabilization of the energy consumption for digging holes under fruit tree seedlings takes place under the condition of fluctuating parameters that determine the characteristics of the digging process.The specified directions of development of hydraulic drives and their components: reduction of dimensions and metal capacity with a simultaneous increase in specific power; energy saving due to increasing the efficiency of hydraulic machines, optimization of circuit solutions; reduction of noise and vibration; simplification of maintenance; increasing reliability and reducing cost.The use of the proposed hydraulic pit digger with an energy-saving hydraulic drive of working bodies will allow to reduce the consumption of fuel and lubricants by up to 15% and increase the quality and productivity of this technological process.
Keywords: fruit tree seedlings; pit; hole digger; hydraulic drive; hydraulic motor; hydraulic cylinder; variable technological load; efficiency; quality